Modelling of stagnant zone formation on diamond cutting tool when turning titanium alloy [electronic resource] - 357141 Thet Thet Mon; Fakulti Kejuruteraan Mekanikal (2007)
Thesis (Ph.D (Kejuruteraan Mekanikal)) - Universiti Teknologi Malaysia, 2007